A phase III randomized trial of high‐dose CEOP + filgrastim versus standard‐dose CEOP in patients with non‐Hodgkin lymphoma: 10‐year follow‐up data: Australasian Leukaemia and Lymphoma Group (ALLG) NHL07 trial. Issue 5 (21st February 2014) - Hertzberg, Mark; Matthews, Jane Palfrey; Stone, Janey Malka; Dubosq, Ming‐Celine; Grigg, Andrew; Ellis, David; Benson, Warwick; Browett, Peter; Horvath, Noemi; Januszewicz, Henry; Abdi, Ehtesham; Green, Michael; et al.
<x xml:space="preserve">Abstract</x> Increasing dose intensity (DI) of chemotherapy for patients with aggressive non‐Hodgkin lymphoma (NHL) may improve outcomes at the cost of increased toxicity. This issue was addressed in a randomized trial aiming to double the DI of myelosuppressive drugs. Between 1994 and 1999, 250 patients with previously untreated aggressive NHL were randomized to treatment with six cycles of 3‐weekly standard (s) or intensive (i) chemotherapy: s‐CEOP–cyclophosphamide 750, epirubicin 75, vincristine 1.4 mg/m2 all on day 1, and prednisolone 100 mg days 1–5; i‐CEOP–cyclophosphamide 1, 500, epirubicin 150, vincristine 1.4 mg/m2 all on day 1, and prednisolone 100 mg days 1–5. Primary endpoint was 5‐year overall survival (OS). Relative to s‐CEOP patients, i‐CEOP patients achieved a 78% increase in the DI of cyclophosphamide and epirubicin. Despite this, there was no significant difference in any outcome: 5‐year OS (56.7% i‐CEOP; 55.1% s‐CEOP; P = 0.80), 5‐year progression free survival (PFS; 41% i‐CEOP; 43% s‐CEOP; P = 0.73), 5‐year time to progression (TTP; 44% i‐CEOP; 47% s‐CEOP; P = 0.72), or complete remission (CR) + unconfirmed CR (CRu) rates (53% i‐CEOP; 59% s‐CEOP; P = 0.64). Long‐term follow up at 10 years also showed no significant differences in OS, PFS, or TTP. The i‐CEOP arm had higher rates of febrile neutropenia (70 vs. 26%), hospitalisations, blood product utilisation, haematological and gastrointestinal toxicities, and lower quality of life scores during treatment, although without significant differences 6‐month later. In the treatment of aggressive NHL in the prerituximab era, increasing DI did not result in improved outcomes, while at the same time lead to increased toxicity. Am. J. Hematol. 89:536–541, 2014. © 2014 Wiley Periodicals, Inc.